Importance: nomenclatural action to restrict the submission of superfluous generic names Tomogonopus (Diplopoda, Spirostreptida, Spirostreptidae) a replacement name for Umbraticus Özdikmen, 2009 (Spirostreptida, Spirostreptidae) - Sierwald, P.; Mauriès, J-P. (Zootaxa, 2017)
Tomogonopus nomen novum Sierwald & Mauriès is introduced as a replacement for Tomogonus Demange, 1971 (pre-occupied by Tomogonus D’Orbigny, 1904, Coleoptera) for an African millipede genus from Sierra Leone (Spirostreptida, Spirostreptidae). A previously introduced generic replacement name, Umbraticus Özdikmen, 2009 (pre-occupied by Umbraticus Voet, 1806, Coleoptera), is invalid. Currently, Tomogonopus n. gen. contains six species, all forming new combinations.